Interdisciplinary research into iron metallurgy along the Drava River in Croatia : the TransFER project - Sekelj Ivančan, Tajana,; Karavidovic̀, Tena, (Archaeopress Archaeology, 2021)
Presenting the results of the TransFER project, this study uses a wide-ranging methodology to examine the evidence for, and nature of, iron production in the lowland area of the central Drava River basin in Croatia during late Antiquity and the early Middle Ages. The results testify to the importance and longevity of iron production in the area.